MODELING INVESTOR BEHAVIOR: INTEGRATING RISK AND RETURN IN A SYSTEM DYNAMICS FRAMEWORK - Jones Parlindungan Nadapdap; Rissa Ayustia; Perminas Pangeran; Eligia Monixa Salfarini; Firdaus Nur (SEAN Institute, 2023)
This research explores the dynamics of investor behavior within the framework of risk and return by proposing Causal Loop Diagrams (CLDs) as a modeling tool. The study delves into the intricate relationships between market sentiment, risk perception, stock prices, and investment decisions. The reinforcing and balancing loops identified in the CLDs highlight the complex interplay of factors that shape investor behavior and market dynamics. The reinforcing loop between positive market sentiment and buying decisions illustrates the strong influence of sentiment on investor actions, potentially leading to prolonged bullish trends. Conversely, the reinforcing loop linking high risk perception to selling decisions depicts a negative cycle, with declining stock prices reinforcing risk perception, triggering further divestment. These loops showcase how market participants respond to changing conditions, stabilizing the market during downturns. Implications of the CLDs include the ability to identify market trends, potential risks, and the influence of investor decisions on market dynamics. Recommendations for market participants, analysts, and policymakers emphasize the importance of understanding market sentiment, implementing prudent risk management, and adapting strategies to changing market conditions. In conclusion, the proposed CLDs offer a valuable tool for comprehending the complexities of investor behavior, contributing to improved investment strategies, enhanced risk management practices, and a deeper understanding of financial market dynamics. This research contributes significantly to advancing our understanding of the intricate factors that shape investor decisions and influence the direction of financial markets.